2009
DOI: 10.1007/s00464-008-0317-y
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic full-thickness resection with laparoscopic assistance as hybrid NOTES for gastric submucosal tumor

Abstract: LAEFR may be considered one of the so-called hybrid natural orifice transluminal endoscopic surgery (NOTES) techniques because a peroral endoscope advances into the peritoneal cavity. LAEFR enabled whole-layer excision as small as possible with an adequate margin. LAEFR is a safe and minimally invasive treatment for patients with gastric SMT, and could be a more reasonable and economical alternative to other laparoscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 14 publications
(20 reference statements)
2
74
0
1
Order By: Relevance
“…Pure EFTR, without laparoscopic procedures, has attracted attention as an extremely minimally invasive treatment. Abe et al first reported full-thickness resection for gastric cancer under laparoscopic and endoscopic guidance, named as laparoscopy-assisted endoscopic full-thickness resection (LAEFR) (11,12). The specific procedure is described as follows.…”
Section: Inverted Lecsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pure EFTR, without laparoscopic procedures, has attracted attention as an extremely minimally invasive treatment. Abe et al first reported full-thickness resection for gastric cancer under laparoscopic and endoscopic guidance, named as laparoscopy-assisted endoscopic full-thickness resection (LAEFR) (11,12). The specific procedure is described as follows.…”
Section: Inverted Lecsmentioning
confidence: 99%
“…Published data are shown in Table 2 (9)(10)(11)(12)(13)(14)(15)(16)(21)(22)(23)(24). The tumor size was 7-60 mm, and the resected specimen size was 22.7-80 mm.…”
Section: Outcomes Of Classical Lecs and Lecs-related Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic full-thickness resection (EFTR) with or without laparoscopic assistance is a promising method to minimize a resection area according to a lesion size [1][2][3][4]. Because a demarcation line of the lesion can be clearly visualized from the inside of the lumen by using endoscopy, the resection area can be optimally determined via this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic full-thickness resection (EFTR) has been invented as a minimally invasive endoluminal surgery for gastrointestinal tumors [1][2][3]. The important characteristic of EFTR is that the margin of the tumor can be definitely checked from the inside with a flexible endoscope and the full layer of the tract is resected, so the resection size can be made smaller and a lesion that has penetrated into the deeper layer of the wall can be resected.…”
Section: Introductionmentioning
confidence: 99%